2007
DOI: 10.1590/s0103-64402007000100017
|View full text |Cite
|
Sign up to set email alerts
|

Importance of occlusion aspects in the completion of orthodontic treatment

Abstract: The purpose of this study was to address the therapeutic goals regarding the static and functional occlusion in the completion of orthodontic treatment. For such purpose, a study population comprising 20 female treated Class II malocclusion subjects with an initial mean age of 11 years underwent a two-phase treatment (orthopedics and orthodontics). The patients were diagnosed in centric relation and were treated according to the six keys for normal occlusion and functional occlusal parameters (centric relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
1
16
1
4
Order By: Relevance
“…There was significant molar relationship correction with treatment, which remained stable at the long-term posttreatment stage 21 (Table 2). Many studies showed the same treatment effects and stability with other orthopedic appliances 15 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There was significant molar relationship correction with treatment, which remained stable at the long-term posttreatment stage 21 (Table 2). Many studies showed the same treatment effects and stability with other orthopedic appliances 15 .…”
Section: Discussionmentioning
confidence: 93%
“…The overbite significantly decreased during treatment and remained stable at the long-term posttreatment stage 21 (Table 2). Similar findings were obtained with other functional appliance therapies 15 .…”
Section: Discussionmentioning
confidence: 96%
“…According to Oltramari et al [52], centric relation (CR) is the position of the jaws in which the condyles have an orthopedic stable position. Thus, for any shift of centric position (CP) intercuspal occlusal position (IOP) causing changes in intercade sagittal relationship, diagnosis, and treatment should be based on the analysis in CR.…”
Section: Discussionmentioning
confidence: 99%
“…Dental professionals must consider the importance of occlusal contacts for the success of dental treatment, maintaining occlusal stability and orofacial harmony, as occlusal interferences may implicate potential damages to the whole stomatognathic system, which includes teeth, supporting structures, neuromuscular system and temporomandibular joints (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%